Effect of fermented jicama extract with Lactobacillus plantarum B1765 as the starter culture on the product quality and total phenolic - Nazarend, Alvisyah; Wikandari, Prima Retno (Journal of Tropical AgriFood, 2023)
This research studied the effect of fermented jicama extract with Lactobacillus plantarum B1765 as a starter culture on the product qualities and Total Phenolic (TP). Fermentation was carried out for 0, 12, 24, and 36 hours at 37oC with 5% (v/v) of starter culture then determine the Total Lactic Acid Bacteria (LAB) were measured using the Total Plate Count (TPC) method, pH, and TTA were measured using a pH meter and acid-base titration, and TP was measured using the Folin-Ciocalteu method. These results showed that the length of fermentation affected increasing total LAB, TTA, TP, and decreasing pH. The best fermentation time in jicama extract was fermented is 24 hours with a total LAB of (9.7±0.31)x107 CFU/mL, pH of 4.21±0.22, TTA of 0.220±0.069%, and TP of 16.22±0.31 mg GAE/g. This value is following the criteria for fermented beverage products. Fermented jicama extract with L. plantarum B1765 potentially increases the TP.